Polycaprolactone-based fibrous scaffolds reinforced with cellulose nanocrystals for anterior cruciate ligament repair - Rocha, Joana M. (2025)
Anterior cruciate ligament (ACL) injuries pose significant challenges, driving the need for innovative repair strategies. Tissue engineering (TE) has emerged as a promising field for ACL injuries. Wet spinning is a filament production technique that enables precise control over filament alignment, diameter, and porosity, making it suitable for developing new scaffolds for ACL injuries. This study develops fibrous scaffolds using wet spinning of polycaprolactone (PCL) reinforced with cellulose nanocrystals (CNC) to enhance mechanical properties. Wet spinning was employed to fabricate fibrous scaffolds, utilizing PCL as the primary polymer due to its favorable biocompatibility and degradability. An automated collector was developed and optimized, which allowed the stretching of the PCL filaments to diameters as low as 30 µm. Several filaments were explored and characterized using SEM, TGA, and mechanical tests. The optimized PCL/CNC filaments were used to develop 3D braided structures that mimic ACL structure. The combination of wet-spun PCL/CNC filaments (with an optimized stirring method) and the braiding procedure allowed for fully biocompatible scaffolds that mimic both the structure and the mechanical properties of native ACL. Cytotoxicity and biocompatibility tests showed cell viability and proliferation values above 99% and 81%, respectively. These findings underscore the potential of CNC-reinforced PCL scaffolds as promising candidates for ACL repair, laying the groundwork for future biomedical applications.